2021
DOI: 10.3390/cancers13051032
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Colonic Tumor Tissue Fusobacterium nucleatum to Predict Staging and Its Interplay with Oral Abundance in Colon Cancer Patients

Abstract: Background. Intestinal microbiota dysbiosis may enhance the carcinogenicity of colon cancer (CC) by the proliferation and differentiation of epithelial cells. Oral Fusobacterium nucleatum (Fn) and Porphyromonas gingivalis (Pg) have the ability to invade the gut epithelium, promoting tumor progression. The aim of the study was to assess whether the abundance of these odontopathogenic bacteria was associated with colon cancer. We also investigated how lifestyle factors could influence the oral Fn and Pg abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 62 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…Over 100 epidemiological studies have been identified in the primary search specifically mentioning F. nucleatum in the abstract. Supplementary Table 10 summarizes the characteristics and main outcomes of 42 of these epidemiological studies which met the eligibility criteria, most of which comparing F. nucleatum presence/abundance in feces from CRC patients versus healthy controls and of tumor tissue versus adjacent normal tissue ( Supplementary Table 10 ; Castellarin et al, 2012 ; Flanagan et al, 2014 ; Fukugaiti et al, 2015 ; Ito et al, 2015 ; Mira-Pascual et al, 2015 ; Wang et al, 2016 ; Xie and Fang, 2016 ; Yu et al, 2016 , 2017 ; Amitay et al, 2017 ; Drewes et al, 2017 ; Eklöf et al, 2017 ; Liang et al, 2017 , 2021 ; Scott et al, 2017 ; Suehiro et al, 2017 ; Yamamura et al, 2017 ; Yoon et al, 2017 ; Hale et al, 2018 ; Hsieh et al, 2018 ; Kwong et al, 2018 ; Repass, 2018 ; Russo et al, 2018 ; Tsuchiya et al, 2018 ; Bundgaard-Nielsen et al, 2019 ; Butt et al, 2019 ; Chen et al, 2019 ; De Carvalho et al, 2019 ; Kageyama et al, 2019 ; Saito et al, 2019 ; Tunsjø et al, 2019 ; Yachida et al, 2019 ; Zhang et al, 2019 ; Alkharaan et al, 2020 ; Boehm et al, 2020 ; Gantuya et al, 2020 ; Kashani et al, 2020 ; Reynolds et al, 2020 ; Eisele et al, 2021 ; Kawasaki et al, 2021 ; Kurt and Yumuk, 2021 ; Pignatelli et al, 2021 ). Two meta-analyses published in 2020 reported pooled ORs of 8.3 for detection of F. nucleatum in colorectal specimens (feces/mucosa/tissue) and being diagnosed with CRC, and 10.06 for detection of F. nucleatum in CRC tissue versus healthy tissue from controls ( Supplementary Table 7 ; Gethi...…”
Section: Resultsmentioning
confidence: 99%
“…Over 100 epidemiological studies have been identified in the primary search specifically mentioning F. nucleatum in the abstract. Supplementary Table 10 summarizes the characteristics and main outcomes of 42 of these epidemiological studies which met the eligibility criteria, most of which comparing F. nucleatum presence/abundance in feces from CRC patients versus healthy controls and of tumor tissue versus adjacent normal tissue ( Supplementary Table 10 ; Castellarin et al, 2012 ; Flanagan et al, 2014 ; Fukugaiti et al, 2015 ; Ito et al, 2015 ; Mira-Pascual et al, 2015 ; Wang et al, 2016 ; Xie and Fang, 2016 ; Yu et al, 2016 , 2017 ; Amitay et al, 2017 ; Drewes et al, 2017 ; Eklöf et al, 2017 ; Liang et al, 2017 , 2021 ; Scott et al, 2017 ; Suehiro et al, 2017 ; Yamamura et al, 2017 ; Yoon et al, 2017 ; Hale et al, 2018 ; Hsieh et al, 2018 ; Kwong et al, 2018 ; Repass, 2018 ; Russo et al, 2018 ; Tsuchiya et al, 2018 ; Bundgaard-Nielsen et al, 2019 ; Butt et al, 2019 ; Chen et al, 2019 ; De Carvalho et al, 2019 ; Kageyama et al, 2019 ; Saito et al, 2019 ; Tunsjø et al, 2019 ; Yachida et al, 2019 ; Zhang et al, 2019 ; Alkharaan et al, 2020 ; Boehm et al, 2020 ; Gantuya et al, 2020 ; Kashani et al, 2020 ; Reynolds et al, 2020 ; Eisele et al, 2021 ; Kawasaki et al, 2021 ; Kurt and Yumuk, 2021 ; Pignatelli et al, 2021 ). Two meta-analyses published in 2020 reported pooled ORs of 8.3 for detection of F. nucleatum in colorectal specimens (feces/mucosa/tissue) and being diagnosed with CRC, and 10.06 for detection of F. nucleatum in CRC tissue versus healthy tissue from controls ( Supplementary Table 7 ; Gethi...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, exposure to blue light with a wavelength of 400–500 nm may have a phototoxic effect on F. nucleatum in multispecies biofilms [ 29 ]. If the proportion of F. nucleatum in the oral cavity can be controlled via violet LED irradiation, it may potentially prevent the development of periodontal disease and colon cancer [ 49 , 50 ]. The detailed mechanism of Fusobacterium species reduction by violet LEDs could not be clarified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory diets, mutagens (NOCs, PAHs, and HCAs), and heme from red meat can damage the intestinal barrier by promoting sulfide-producing bacteria and mucin-degrading bacteria, such as A. muciniphila ( Ijssennagger et al., 2015 ; Mehta et al., 2019 ; Pignatelli et al., 2021 ). Ijssennagger et al.…”
Section: Gut Dysbiosis and Intestinal Barrier Dysfunctionmentioning
confidence: 99%
“…This cascade of events results in the activation of the Wnt signaling pathway, which increases the risk of CRC. Liu L. et al (2018) and Pignatelli et al. (2021) found that F. nucleatum triggers colorectal tumorigenesis through the activation of the Wnt pathway ( Liu L. et al., 2018 ).…”
Section: Gut Dysbiosis and Intestinal Barrier Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation